Strategic Code-Switching in Indonesian EFL Classroom: Forms, Functions, and Students Perspective - Yunita Maharani Azzahra; Aridah Aridah; Maria Teodora Ping; Syamdianita Syamdianita; A.K. Amarullah (Borneo Educational Journal (Borju), 2026)
This study examined the forms and functions of lecturers’ code-switching in English as a Foreign Language (EFL) classroom interaction in Indonesian higher education. Using a qualitative descriptive design, data were collected through classroom observations and student interviews and analyzed thematically. The study focused on naturally occurring interactions across multiple lessons to capture authentic language use. The findings reveal three main forms of code-switching: inter-sentential, intra-sentential, and tag switching, with inter- and intra-sentential appearing more salient during explanatory and instructional sessions. Functionally, code-switching was used toexplain material, give instructions, check understanding, build rapport, and manage classroom behavior. Students reported that code-switching supported their understanding while still maintaining the use of English as the main instructional language. These results indicate that lecturers’ code-switching is a patterned and interactionally grounded practice, demonstrating how bilingual resources can be effectively leveraged to enhance learning outcomes and student engagement in Indonesian EFL classrooms.